Geometric Evaluation of GeoTIFF Worldview-2 Image Data Acquired Over Sea of Marmara - G. Buyuksalih; C. Gazioglu; K. Jacobsen (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
A WorldView-2 GeoTIFF image was used to analyse the potential information for marine application in the Sea of Marmara and the surrounding land. The first problem to be solved was scene orientation, as the GeoTIFF image was not an ortho image but a simple projection to the sea level. The Rational Polynomial Coefficients (RPC) provided with the image did not match the delivered image; orientation by 3D-transformation was required and successful. The possibility of obtaining depth information by stereoscopic survey and the use of radiometric information related to the water depth are explained with some examples. A typical problem when using images is the total reflection of the sun light by the water surface, which is magnified by small waves. This requires images taken in the opposite direction of the sun. In general, the depth information is limited by water turbidity.